Temporal patterns, benefits, and defensive behaviors associated with male parental care in the glassfrog Centrolene savagei. Issue 2 (3rd March 2020) - Ospina-L, Ana M.; Navarro-Salcedo, Paula; Rios-Soto, Julián A.; Duarte-Marín, Sebastián; Vargas-Salinas, Fernando
Abstract : Anurans are good study models for a better understanding of the behavioral ecology of parental care in vertebrates because such behavior evolved multiple times independently in frogs and toads; moreover, forms of parental care are highly diverse in those vertebrates and according to the species is performed by the male, the female, or both sexes. In this study, we first recorded variations in parental care by males of the glassfrog Centrolene savagei at two temporal scales (day vs night, and throughout embryo development). Second, we compared levels of embryo mortality in egg clutches attended and naturally unattended by males. Third, we performed field experiments to simulate the risk of predation by small invertebrates to test the level of male commitment to providing parental care. During 65 field trips (1–2 nights each) we recorded 87 males and 154 egg clutches in a population of C. savagei from the Central Andes of Colombia. Parental care (measured as male egg brooding) was higher at night than at day, and it decreased from oviposition towards egg hatching as embryos developed. Embryo mortality was greater in naturally abandoned clutches, compared to those receiving male care. Most males caring for eggs but none of the solitary males exhibited defensive behavior, such as biting and kicking the predator stimulus. Preliminary results also suggest that caring males have a higher tolerance toward threatening stimuli before fleeing than did solitary males. Altogether, rates of natural mortality suggest that male care for eggs is likely adaptive in this species. Males protect their offspring from at least two causes of mortality: desiccation and predation. However, when and how much males care for the offspring varies between night and day, and through embryonic development.